2017
DOI: 10.1364/oe.25.031948
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the damage resistance of ultra-fast optics by novel design approaches

Abstract: Dielectric components are essential for laser applications. Chirped mirrors are applied to compress the temporal pulse broadening crucial in the femtosecond regime. However, the design sensitivity and the electric field distribution of chirped mirrors is complex often resulting in low laser induced damage resistances. An approach is presented to increase the damage resistance of pulse compressing mirrors up to 190% in the NIR spectral range. Layers with critical high field intensity of a binary mirror design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Substituting this high refractive index layer by a nanolaminate structure the maximum field intensity in Ta 2 O 5 could be dropped by a factor of 1.95. The LIDT could be improved by almost 190 % with respect to the binary chirped mirror [26]. In addition the application of dielectric nanolaminates offers the possibility to sputter single binary layers to tune the optical gap.…”
Section: Application Of Nanolaminates In Hr-mirrorsmentioning
confidence: 99%
“…Substituting this high refractive index layer by a nanolaminate structure the maximum field intensity in Ta 2 O 5 could be dropped by a factor of 1.95. The LIDT could be improved by almost 190 % with respect to the binary chirped mirror [26]. In addition the application of dielectric nanolaminates offers the possibility to sputter single binary layers to tune the optical gap.…”
Section: Application Of Nanolaminates In Hr-mirrorsmentioning
confidence: 99%
“…The laser-induced damage threshold (LIDT) of optical components represents the limiting factor of the useful performance of ultrafast solid-state lasers. 1,2 To improve the LIDT of optical materials, especially optical coatings, considerable efforts have been made to test diverse materials, [3][4][5] develop new optimized coating designs, [6][7][8] and advanced fabrication methods. [9][10][11] Among the plethora of thin-film growth techniques, pulsed-laser deposition (PLD) is considered to be one of the most versatile and powerful.…”
Section: Introductionmentioning
confidence: 99%
“…Laser systems are increasingly improving, therefore demands are growing for optical elements such as high reflective (HR) mirrors, antireflective coatings in terms of resistivity to laser radiation. Many investigations are done in order to improve existing optical coatings including electric field distribution optimization [1,2] in formation of multilayers structure, laser conditioning procedures of optical elements [3] or design new and innovative material engineering methods [4]. Tolenis et al group already demonstrated the possibility to create nano-structured films, which are capable to withstand up to 60 J/cm 2 at 355 nm wavelength ns pulses [5], however, the main limitation includes high number of defects.…”
Section: Introductionmentioning
confidence: 99%